Cynism pada Karyawan RSUD Ahmad Yani Kota Metro - Oksa Lawdy Tanjung (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research summarizes and analyzes literature related to employee cynicism in the context of the work environment. Cynicism, as an attitude of skepticism and disdain for trust in organizational processes, has become a focus of increasing attention in the world of human resource management. Through a careful literature review, this research explores various aspects of employee cynicism, identifies causal factors, and analyzes the consequences for individuals and organizations. The literature indicates that employee cynicism may emerge in response to unclear organizational policies, revealed transparency, or inequities in careeropportunities. The impact of employee cynicism on includes decreased performance, increased turnover, and decreased organizational engagement. Some literature also highlights management efforts that can be taken to overcome cynicism, such as improving internal communication, providing clear feedback, and creating a supportive organizational culture. This literature review shows the need for special attention to employee cynicism in efforts to create a positive and productive work environment. Future research could focus on developing management strategies that can reduce levels of cynicism, increase job satisfaction, and strengthen relationships between employees and organizations. Thus, this research provides useful insights for human resources practitioners and organizational leaders seeking to improve employee well-being and productivity.